Debt Maturity Management - Hu, Yunzhi; Varas, Felipe; Ying, Chao (Review of Financial Studies, 2026)
Abstract This paper studies how a borrower issues long- and short-term debt in response to shocks to the fundamental value. Short-term debt protects creditors from future dilution and incentivizes the borrower to reduce leverage after small negative shocks. Long-term debt postpones default and allows the borrower time to recover after large negative shocks. When borrowers are in distress, they rely on short-term debt; however, they issue both types of debt during more normal periods. Our model generates novel implications for the dynamic adjustment of debt maturities.